Desain Pembelajaran Materi Fiqih dalam Perspektif Kurikulum Merdeka Belajar - Seten Hartedi (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2023)
This study aims to answer a number of problems related to learning Fiqh material which seems monotonous and boring, if you look at it and examine it, it actually exists in material that does not change from year to year and does not have renewal, because fiqh material is learning that focuses on religious subjects. Islam, of course, cannot change because it has absolute law. This is what researchers are trying to see, but from a curriculum perspective, namely, an independent learning curriculum that offers new concepts in it. In the process of this research, the research process will use qualitative methods with descriptive research. In this research, journal or book review data will be used as study material related to this research. And the results of the discussion in this study show that the independent learning curriculum is a curriculum that focuses on the learning process that is free according to the teacher’s creations in teaching, this can be seen in the learning design which focuses on teaching devices in all subjects, for example on fiqh material in the sub-teaching thaharah or purification, the teacher can teach the thaharah material with combined teaching tools or the latest teaching devices according to the characteristics of students and the availability and suitability of learning objectives, which of course this will be able to improve the professionalism of a teacher.